SOSIALISASI PEMASANGAN BATAS TANAH DI KABUPATEN BOYOLALI YANG BERASAL DARI JUAL BELI SECARA NEGOSIASI - Kartika Cahyaningtyas; Nafi’uddin Fauzi Mahfudh; Nindi Nur Fadya; Veronica Kinanthi Sihutami (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
This activity aims to implement one of the Tri Dharma of Higher Education in the form of community service. The hope is that the community can resolve legal issues related to the transfer of rights arising from sales and purchases effectively and efficiently, avoiding resorting to court, but rather through negotiation. The legal basis for negotiation is stipulated in Article 1 Paragraph 10 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The method used is advocacy, which includes: awareness of the problem, interest in participating in resolving the problem, concern for the resolution, and agreement to resolve the problem. The impact of this activity is that after an agreement is reached through the negotiation process, the land sale and purchase transaction continues until the issuance of the certificate by the Boyolali Regency Land Office, which requires completing the required documents at the Boyolali Regency Land Office. This is important because the legal transfer of rights occurs only after the processing by the Boyolali Regency Land Office. Keywords: Negotiation, Transfer of Rights, Sale and Purchase